2018
DOI: 10.31248/jasp2018.104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climate smart agricultural practices on poverty status of maize rural farming household in Sokoto State, Nigeria

Abstract: The current level of poverty in Nigeria is disturbing and climate change impends food security and increases poverty indirectly and directly on individuals or households. Farming households are changing agricultural practices as a result of global observation of climatic and environmental changes. This research work recognised a link which exists between climate change, climate smart agricultural practices (CSAP) and poverty status of farming households in North West Nigeria. The objective of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The deployment of cell phone technology has not been optimized to its fullest potentials in the Northwest zone of Nigeria as unveiled by Khidir (2019) in a study to ascertain the awareness and usage status of mobile phone apps by farmers in the region. Despite the fact that the zone is recognized as an agricultural centre of the nation, with the majority of people from the zone engaging primarily in farming as their main source of livelihood (Olapojo, 2012;Ekpa, 2017;Ekpa, Oladele and Akinyemi, 2017), the zone is acknowledged Tobit regression model was used to compute factors that influence the rate at which the farmers use mobile phone apps at their disposal. The Tobit model is specified as follows: Y*= Xiβ + ε ……………………………………………………………………………….…”
Section: Introductionmentioning
confidence: 99%
“…The deployment of cell phone technology has not been optimized to its fullest potentials in the Northwest zone of Nigeria as unveiled by Khidir (2019) in a study to ascertain the awareness and usage status of mobile phone apps by farmers in the region. Despite the fact that the zone is recognized as an agricultural centre of the nation, with the majority of people from the zone engaging primarily in farming as their main source of livelihood (Olapojo, 2012;Ekpa, 2017;Ekpa, Oladele and Akinyemi, 2017), the zone is acknowledged Tobit regression model was used to compute factors that influence the rate at which the farmers use mobile phone apps at their disposal. The Tobit model is specified as follows: Y*= Xiβ + ε ……………………………………………………………………………….…”
Section: Introductionmentioning
confidence: 99%
“…The other piece of advice from the donor and supported by the INGO head office was to suggest that the community be encouraged to move away from maize as a staple, given the marginal environment in which it was grown. As I noted in my report, moving away from established food staples is a fraught process in any society and has little if any record of success anywhere (Ekpa 2018;Kilby 2019). Local communities are best placed to determine the best food crops for their particular context, and the focus of external support should be to improve existing systems, a lesson that aid donors across the board seem to have trouble learning (Gliessman 2020).…”
Section: Semi-arid Agriculture In An Hiv/aids Contextmentioning
confidence: 94%
“…The majority of the rural women indicated they engaged in other nonagricultural income-generating activities such as business/trading (62.52%), civil service (21.89%), pensioners (3.13%), while 12.5% of the respondents had no other income generating activity aside farming. This may result to low uptake of climate change adaptation strategies because some studies (Akwiwu 2018, Ekpa andOladele, 2018;Adebayo and Ojogu, 2019;Terdoo, 2020) have shown that when people have other alternative means of livelihood to agriculture, they may show lackadaisical attitude towards climate change issues which affect agriculture. Majority (40.63%) of the rural women indicated they had taken Senior Secondary Certificate Examination (SSCE) and had O level.…”
Section: Socio-economic Characteristics Of the Rural Womenmentioning
confidence: 99%